A Demographic Profile of Candidates Taking the Graduate Management Admission Test During 1980-81 - Leary, Linda F.; Wightman, Lawrence E.; Graduate Management Admission Council, Princeton, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
This publication reports demographic data describing the population of examinees who took the Graduate Management Admission Test (GMAT) during the administration year October 1980 through July 1981. This information was obtained from examinee responses to the nine-item Biographical Information Questionnaire, other information on the 1980-81 registration form and test scores from the examinee records. The non-mandatory questionnaire requested information about the examinees' citizenship, residence, primary language, subgroup affiliation, work experience, age and sex. Three types of demographic information were gathered from the examinees: geographic data, academic data and biographical data. Data from the 214,555 records of examinees who took the GMAT at one or more of the four administrations during 1980-81 are summarized in the thirty-seven tables included in this report. (PN)
Availability: Graduate Management Programs, Box 2886, Educational Testing Service, Princeton, NJ (No Charge).
Microfiche.
Keywords: Biographical Inventories; Business Administration Education; College Entrance Examinations; Demography; Educational Research; Educational Trends; Graduate Study; Higher Education; Profiles; Questionnaires; School Statistics; Statistical Data; Student Subcultures; Trend Analysis; Candidates -- Graduate Management Admission Test; Reports, Research; Numerical/Quantitative Data